2020
DOI: 10.3390/ijerph17093338
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Retirement Decisions in Denmark: Comparing Employees Who Expect to Retire before, at, and after the State Pension Age

Abstract: Aim: Analyse factors affecting retirement decisions comparing employees expecting to retire before, at, and after the state pension age. Methods: In the SeniorWorkingLife cohort, 12,269 workers aged +50 replied to questions about expected retirement age, reasons for leaving, and reasons for staying longer. Results: For all groups, poor health, wish for more leisure, and economy were the most salient expected reasons for retiring. Many would stay longer if there were better possibilities for more leisure time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…Having one or more disease was associated with intention to retire early. This finding is in line with earlier findings which shows that poor physical health is an expected reason for retiring (Meng et al 2020;Wahrendorf et al 2017). Another recent study from Sweden reported that people with better health and positive work prospects were less likely to support retiring earlier (Sousa-Ribeiro et al 2021).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Having one or more disease was associated with intention to retire early. This finding is in line with earlier findings which shows that poor physical health is an expected reason for retiring (Meng et al 2020;Wahrendorf et al 2017). Another recent study from Sweden reported that people with better health and positive work prospects were less likely to support retiring earlier (Sousa-Ribeiro et al 2021).…”
Section: Discussionsupporting
confidence: 89%
“…The retirement decision is complex and needs to be seen from multiple perspectives as it involves multiple factors and aspects of life. Studies have highlighted the role of family, life partners or close friends (Nilsson et al 2011) and work-life balance (Meng et al 2020) on the retirement decision. Factors outside of work such as enjoying life, having increased flexibility, more time to spend with a spouse and grandchildren, and taking care of others, have also been studied in relation to retirement intentions (Reeuwijk et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it should be noted that the Nagelkerke R Squares were quite low (see Tables 3 and 4 ), indicating that besides prior SA, DP, and the sociodemographic covariates, there were other factors that can explain work participation past the age of 65 than those accounted for in this model. Such factors could, e.g., be influence by significant others [ 15 , 55 ], the employer [ 11 ], societal and group norms regarding retirement [ 56 ], work environment [ 22 , 51 ], motivation to continue in paid work [ 22 ], personality [ 57 ], type of morbidity, as well as duration, rate (part- or full-time), and number of SA and DP spells. Moreover, one limitation is the possible overlap between SA and DP, which might affect the results of the analysis in which SA and DP were separate exposure variables.…”
Section: Discussionmentioning
confidence: 99%
“…Pension decisions are also influenced by factors related to the design of the social security system [ 51 , 52 , 53 ]; including the statutory retirement age [ 36 , 44 , 54 , 55 , 56 , 57 ] and the ongoing reforms of pension systems [ 58 ]. Factors of an individual nature include: health status [ 22 , 39 , 50 , 59 , 60 , 61 , 62 , 63 , 64 ]; life expectancy [ 65 , 66 ]; characteristics of work and occupation [ 59 , 67 , 68 , 69 ]; job satisfaction [ 63 , 70 , 71 , 72 ]; marital status and family conditions, including caring responsibilities [ 50 , 73 , 74 , 75 ]. The decision to retire may also be influenced by the wish for more leisure [ 64 ].…”
Section: Literature Review—neoclassical and Behavioral Determinants O...mentioning
confidence: 99%